DEVELOPMENT OF INTEGRRATED SCIENSE E-MODUL ON INQUIRY BASED LEARNING ON SIENCE OBJECK MATERIALS AND OBSERVATIONS - Sautul hamid, Sautul Hamid; S.Pd.M.P.d., Khairil Arif (Department of Science Education, 2024)
This study discusses the Development of Inquiry-Based Integrated Science E-Modules on Natural Science Object Material and Observations, where this research aims to produce Inquiry-based learning E-modules that can help students increase their interest in learning and as additional teaching materials in understanding Science Objects material and their Observations , as well as investigating the validity and practicality of Inquiry-Based Integrated Science E-Module on Natural Science Object Material and Observations. The type of research used is Research and Development (R&D) with the ADDIE development model which consists of five stages namely Analysis, Design, Development, Implementation, and Evaluation but is limited to the Development stage. The research instrument consisted of teacher observation sheets, student observation sheets, validity test questionnaires and practicality test questionnaires. The data obtained were analyzed using a formula to analyze the results of validity and practicality tests. The results of the validity test obtained an average Likert scale value of 92% with a very valid validity category. The results of the practicality test on teachers obtained an average Likert scale score of 96% with a very practical validity category and the results of the practicality test on students obtained an average Likert scale score of 87% with a very practical validity category. Based on these results, it was concluded that the Inquiry-based Integrated Science E-module on Natural Science Objects and their Observations is valid and practical.